PENGARUH PEMBELAJARAN PRAKTIK DAN MOTIVASI BERWIRAUSAHA TERHADAP SIKAP KEWIRAUSAHAAN SISWA SMK NEGERI BIDANG TEKNOLOGI DAN REKAYASA DI KOTA SEMARANG - Savitri, Savitri (Educational Management, 2012)
Abstract: In a developing country, students at vocational high schools have important roles. Through exercises and practices in their schools or industry, we expect that they have entrepreneurship motivation. Entrepreneurship attitude of students can produce productivity which is beneficial for themselves, society, and country. Population for this research is vocational high school students in Semarang majoring in technology and engineering. There were 2607 students in Semarang. This study employed 304 students as a sample. The conclusions of this research are there are positive and significant effects of practices to entrepreneurship attitude of vocational high school students with determination (R2) = 40.6%, (2) there are positive and significant effects of entrepreneurship motivation to entrepreneurship attitude of mechanical high school student with determination (R2) = 22.5%, (3) there are positive and significant effects of practices and entrepreneurship motivation to entrepreneurship attitude of mechanical high school students with determination (R2) = 43.1%. The regression equation is Y = 33.042 + 0.572X1 + 0.276X2. Practice has bigger influence than entrepreneurship motivation to entrepreneurship attitude. Â  Abstrak: Dalam negara yang sedang membangun, siswa SMK memiliki peranan yang penting. Melalui latihan dan praktik kerja di sekolah maupun di dunia usaha dan dunia industri diharapkan motivasi berwirusaha tumbuh. Sikap kewirausahaan akan melekat pada diri siswa, dapat menghasilkan produktivitas kerja yang dapat berguna bagi diri sendiri, masyarakat dan bangsa. Populasi penelitian ini adalah siswa SMK Negeri Bidang Teknologi dan Rekayasa di Kota Semarang sebanyak 2607 siswa, sebagai sampel penelitian diambil 304 siswa. Hasil penelitian menunjukkan terdapat pengaruh positip dan signifikan antara pembelajaran praktik terhadap sikap kewirausahaan siswa dengan dengan determinasi (R2) = 40,6%, (2) terdapat pengaruh positip dan signifikan antara motivasi berwirausaha terhadap sikap kewirausahaan siswa dengan dengan determinasi (R2) = 22,5%, terdapat pengaruh positip dan signifikan antara pembelajaran praktik dan motivasi berwirausaha terhadap sikap kewirausahaan siswa dengan dengan determinasi (R2) = 43,1%. Persamaan regresi Y= 33,042 + 0,572 X1 + 0,276 X2 . Pembelajaran praktik memiliki pengaruh yang besar dibandingkan motivasi berwirausaha terhadap sikap kewirausahaan.